2003
DOI: 10.1063/1.1559659
|View full text |Cite
|
Sign up to set email alerts
|

Deep ultraviolet picosecond time-resolved photoluminescence studies of AlN epilayers

Abstract: AlN epilayers with high optical qualities have been obtained by metalorganic chemical vapor deposition on sapphire substrates. Deep UV picosecond time-resolved photoluminescence (PL) spectroscopy has been employed to study the optical transitions in AlN epilayers. Two PL emission lines associated with the donor bound exciton (D0X, or I2) and free exciton (FX) transitions have been observed, from which the binding energy of the donor bound excitons in AlN epilayers was determined to be around 16 meV. Time-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 12 publications
8
72
2
Order By: Relevance
“…These defect levels may at the same time provide efficient relaxation channels for energy back transfer to the AlN host. 26 The PL data presented here are quite different than results of CL measurements done on similar Gd-implanted AlN thin films. [20][21][22] While both PL and CL measurements yield an intense UV emission at 318 nm, only the CL measurements have shown evidence of Gd 3+ transitions at other wavelengths, near 259 and 285 nm, arising from higher energy manifolds.…”
Section: -contrasting
confidence: 49%
“…These defect levels may at the same time provide efficient relaxation channels for energy back transfer to the AlN host. 26 The PL data presented here are quite different than results of CL measurements done on similar Gd-implanted AlN thin films. [20][21][22] While both PL and CL measurements yield an intense UV emission at 318 nm, only the CL measurements have shown evidence of Gd 3+ transitions at other wavelengths, near 259 and 285 nm, arising from higher energy manifolds.…”
Section: -contrasting
confidence: 49%
“…The binding energy of the free exciton in wurtzite AlN is less than 0.1 eV, so the optical and fundamental band gaps are within 0.1 eV. 32 We found that by varying the screening parameter in the HSE functional to 0.05 from 0.2 1/Å we reproduce the experimental band gap at 0 K but the ionization energies of acceptors also shift up by about 0.25 eV independently of the defect. This would indicate a slight deviation between the calculated and measured thermal ionization energies for Mg defect.…”
supporting
confidence: 59%
“…Additional broader peaks were observed at 3.040 and 3.410 eV and were previously related to deep-level oxygen impurities. [14][15][16] Two additional relatively small peaks were observed near 4.5 eV and are likely related to carbon impurities in AlN. 1,14,15 This relatively weak emission demonstrates that only a minor carbon contamination occurred during sample growth.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Two additional relatively small peaks were observed near 4.5 eV and are likely related to carbon impurities in AlN. 1,14,15 This relatively weak emission demonstrates that only a minor carbon contamination occurred during sample growth. 16 The depth-resolved analysis of the CL spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%